2009
DOI: 10.1136/hrt.2009.177238
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy: reduction of blood pressure already in the normal range further regresses left ventricular mass

Abstract: ISRCTN48331653.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
6
19
0
1
Order By: Relevance
“…Similarly, although the study was only of 6-month duration, reductions in blood pressure in previous studies have been seen within a few weeks of large oral doses of vitamin D. Reduction in LV mass on MRI has been demonstrated within 9 months with other vascular interventions, for instance by previous studies on allopurinol and on blood pressure reduction. 21,22 However, our results are consistent with the main findings of the PRIMO (Paricalcitol Capsule Benefits in Renal FailureInduced Cardiac Morbidity) trial, which showed no effect of 48 weeks of paricalcitol therapy on LV mass in patients with advanced kidney disease. 14 Changes in left atrial volume may provide a more sensitive early measure of cardiac remodeling, and a substudy of PRIMO did find a reduction in left atrial volume with paricalcitol therapy 23 ; we were unable to demonstrate this in the current study although the number of patients with usable left atrial volumetric information was low.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, although the study was only of 6-month duration, reductions in blood pressure in previous studies have been seen within a few weeks of large oral doses of vitamin D. Reduction in LV mass on MRI has been demonstrated within 9 months with other vascular interventions, for instance by previous studies on allopurinol and on blood pressure reduction. 21,22 However, our results are consistent with the main findings of the PRIMO (Paricalcitol Capsule Benefits in Renal FailureInduced Cardiac Morbidity) trial, which showed no effect of 48 weeks of paricalcitol therapy on LV mass in patients with advanced kidney disease. 14 Changes in left atrial volume may provide a more sensitive early measure of cardiac remodeling, and a substudy of PRIMO did find a reduction in left atrial volume with paricalcitol therapy 23 ; we were unable to demonstrate this in the current study although the number of patients with usable left atrial volumetric information was low.…”
Section: Discussionsupporting
confidence: 82%
“…Более того, было продемонстрировано снижение массы миокарда у пациентов с ГЛЖ даже в отсутствии повышенного давления [17]. Одним из немногочисленных исследований в области эво-люции раннего ПОМ у пациентов с метаболическими нарушениями является работа Gomez-Marcos с соав-торами, которые зарегистрировали повышение элек-трографических признаков ГЛЖ, а также снижение ЛПИ и СРПВ.…”
Section: Discussionunclassified
“…26 In meta-analysis, the absolute reductions in LV mass were 22.8 gm with β-blockers with similar figures for calcium antagonists and diuretics, although ACEIs were twice as potent. 27 Further regression of LVH in such normotensive patients is likely to reduce future cardiovascular events.…”
Section: Treatment Of Residual Risk: Lvhmentioning
confidence: 99%